2021
DOI: 10.24235/al.ibtida.snj.v8i2.8253
|View full text |Cite
|
Sign up to set email alerts
|

Development of Web E-Scaffolding Based on Scientific Explanation as Teaching Materials for Primary School Pre-service Teachers

Abstract: Science learning does not only involve facts and concepts but also ways of thinking, explaining scientifically, and doing a practicum. Unfortunately, existing e-learning and/or social media have not been able to facilitate the implementation of online practicums. Therefore, an e-scaffolding website based on scientific explanations is needed as teaching media and materials since learning is mostly conducted online during the Covid-19 pandemic. This study aims to describe the development process and the validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The results showed that physics learning with procedural e-scaffolding improved students' scientific explanations, specifically claims, evidence, and reasoning. In reference [46], a scientific explanation-based e-scaffolding website was developed by integrating PhET simulations as a virtual practicum. The results showed that it significantly improved students' ability to produce scientific explanations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that physics learning with procedural e-scaffolding improved students' scientific explanations, specifically claims, evidence, and reasoning. In reference [46], a scientific explanation-based e-scaffolding website was developed by integrating PhET simulations as a virtual practicum. The results showed that it significantly improved students' ability to produce scientific explanations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using e-modules in the learning process can improve thinking skills, effectiveness, innovation, and fun conditions in learning (Purnamasari, 2018;Waluya et al, 2022). Learning with interactive e-modules can convey all material according to learning targets (Amelia, 2021;Maielfi, 2021;Priantini & Widiastuti, 2021). Moreover, with high flexibility, students can study material in advance through digital devices anywhere and anytime (Kurniawan et al, 2019;Sidiq & Suhendro, 2021).…”
Section: Characteristics Of Teaching Materialsmentioning
confidence: 99%
“…While the results of the product readability test were 82.29%. This means that the development of an e-scaffolding website based on scientific explanations is very valid and very feasible to use in developing the scientific explanation abilities of prospective elementary school teachers (Amelia, 2021) . Furthermore, Umbara Research Results with different score criteria, namely The results of the development show the the average value of the media expert validation test was 4.62 (Umbara et al, 2021) , and the fitri research on media expert validation was categorized as very feasible.…”
Section: mentioning
confidence: 99%